STUDENTS’ PERSPECTIVES ON USING TELEGRAM MESSENGER AS A LEARNING MEDIA - Sri Wahyuni (Universitas Lancang Kuning, 2018)
A learning media is very important to support a course to achieve the learning objective. This study deals with how are students’ perspectives on using Telegram Messenger that used as a learning media at English Study Program of Universitas Islam Riau. This research was a descriptive qualitative research. It was conducted at Universitas Islam Riau at Jalan Kaharuddin Nasution No. 133 Pemberhentian Marpoyan, Pekanbaru-Riau from January until May 2017 with the samples were the fifth semester students at English Study Program. The research instrument in this research was a questionnaire that consists of 20 statements of (1) perceived usefulness (2) perceived ease to use (3) attitude toward using (4) actual system use. Further, to get the information related to four indicators in this research, the researcher employed likert scale, 5 was given for strongly agree (SA), 4 for agree (A), 3 for undecided (U), 2 for disagree (D), and 1 for strongly disagree (SD). The questionnaire used close-ended question in online questionnaire, asking the respondent to get students’ perspective on using Telegram Messenger by checking one check box in Survey Monkey. The students’ perspectives in perceived ease of use for strongly agree which was 35%, perceived usefulness for strongly agree was 22%, attitude toward usage for strongly agree was 30%, actual system use for strongly agree was 19%, actual system use for strongly agree was 19%. In other words, respondent positively responded.